The bandwidth and jitter study in EPON upstream traffic - Radzi N.A.M.; Din N.M.; Majid M.S.A.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Quality of Service (QoS) is of concern in Ethernet Passive Optical Network (EPON) in supporting real time traffic. This paper describes a centralized dynamic bandwidth allocation (DBA) algorithm in supporting the QoS inside both the optical line terminal and optical network units for upstream traffic. The DBA algorithm is called Universal DBA and it has been compared with other DBA algorithm to prove its advantages in terms of bandwidth utilization and jitter. It shows that UDBA algorithm improves as high as 14.7% in terms of bandwidth utilization and 17.7% in terms of jitter. 2013 IEEE.